DETERMINING SELLING PRICE USING FULL COSTING AND VARIABLE COSTING METHODS AT EKA JAYA OPAK FACTORY - Rispa Amelia; Sugianto; Hendra Harmain (International Journal of Cultural and Social Science, 2025)
This study aims to assess the accuracy of production cost calculations, which serve as the foundation for determining an appropriate cost of sales. A descriptive qualitative approach was employed, with data collected through direct observation and interviews. The data includes production details, raw material costs, labor costs, and factory overhead costs over a specified period. The study highlights the potential impact of pricing strategies on consumer behavior: a selling price that is too high compared to competitors may lead consumers to opt for cheaper alternatives, while an excessively low price risks underpricing. The findings revealed significant discrepancies in production cost calculations. The company's simplified method resulted in lower costs compared to both the variable costing and full costing methods. The difference between the company's method and full costing suggests the potential for underpricing, as it neglects certain cost components, particularly fixed overhead costs. In contrast, the full costing method offers a more comprehensive and accurate cost analysis, which is crucial for determining sustainable and competitive selling prices.